Retinal and vitreoretinal surgery : mastering the latest techniques - Retinal and vitreoretinal surgery; Boyd L., Samuel; Drews, Robert C. (Panamá : Highlights of ophthalmology, 2002)
Su objetivo es ayudar a miles de pacientes con enfermedades oculares que se beneficiarán de los avances científicos más avanzados presentados en nuestras publicaciones.
Incluye índice
CONTENTS SECTION I: DIAGNOSTIC TECNIQUES SECTION II: PRACTICAL AL ASPECTS OF LASER PHOTOCOAGULATION SECTION III: THE LEADING ACHIEVEMENTS IN VITREORETINAL SURGERY SECTION V: RETINAL VASCULAR DISEASES AND OHTERS MORE
Keywords: ENFERMEDADES DE LA RETINA; OFTALMOLOGÍA; OPHTHALMOLOGY